Variability of heat and salinity content in the North Atlantic in the last decade - V. O. Ivchenko; N. C. Wells; D. L. Aleynik; A. G. P. Shaw (Ocean Science, 2010)
The analysis of the heat and salinity contents has been made for the Northern Atlantic for the decade between January 1999 and December 2008. This analysis is based on the Argo profiling data for the upper 2000 m. Basin-averaged values of heat content deviation (HCD) and salinity content deviation (SCD) are robust and stable. The HCD and SCD demonstrate positive trends in the last decade in the upper 2000 m of the North Atlantic. The linear trend of HCD and SCD are (11.14±3.17)×10 20 J/yr, and (2.80±1.17)×10 13 kg/yr, respectively. Both trends are significant at 95% level of significance.